Prognostic and clinicopathological value of MUC1 expression in colorectal cancer: A meta-analysis. Issue 9 (March 2019) - Li, Chao; Liu, Tao; Yin, Libin; Zuo, Didi; Lin, Yuyang; Wang, Lei
Abstract: Background: Accumulating evidence supports the overexpression of mucin 1 (MUC1) in colorectal cancer (CRC), but the value of elevated MUC1 expression remains controversial. Here, we evaluated the prognostic and clinicopathological value of MUC1 expression in CRC. Materials and methods: The Web of Science, PubMed, Embase, Cochrane Library, and Wanfang databases, as well as the China Biology Medicine disc (CBMdisc) and China National Knowledge Infrastructure (CNKI) were searched for studies on MUC1 expression and prognosis of CRC through July 20, 2018. The pooled relative risks (RRs) and hazard ratios (HRs) with 95% confidence intervals (95% CIs) were calculated to evaluate the prognostic and clinicopathological value of MUC1 expression in CRC. The Revman version 5.3 package and STATA, version 12 were employed for pooled analysis and analysis of publication bias. Results: This meta-analysis included 16 published studies. The combined analysis showed that CRC patients with high MUC1 expression had a worse clinical outcome in overall survival (OS) (HR = 1.51, 95% CI = 1.30–1.75, P  <.00001). In addition, high MUC1 expression was associated with higher TNM stage (RR = 1.44, 95% CI = 1.17–1.77, P  = .0007), greater depth of invasion (RR = 1.30, 95% CI = 1.10–1.53, P  = .002), and lymph node metastasis (RR = 1.47, 95% CI = 1.20–1.80, P  = .0002) of CRC. However, the elevated MUC1 expression was not related to disease-free survival/recurrence-free survival (DFS/RFS) (HR = 1.51, 95% CI = 0.78–2.89, P  = .22), histological grade (RR = 1.15, 95% CI = 0.96–1.38, P  = .12), gender (RR = 0.95; 95% CI = 0.83–1.08, P  = .44), tumor size (RR = 1.11, 95% CI = 0.85–1.44, P  = .44), tumor site (RR = 1.01, 95% CI = 0.88–1.16, P  = .84), or mucinous component (RR = 0.83, 95% CI = 0.60–1.14, P  = .24) in CRC. Conclusion: Our findings indicated that high MUC1 expression represents a marker of poor prognosis in CRC. Meanwhile, elevated MUC1 expression was associated with advanced TNM stage, greater depth of invasion, and lymph node metastasis. Abstract : Supplemental Digital Content is available in the text